A proprietary GMP human platelet lysate for the expansion of dermal fibroblasts for clinical applications. (2nd January 2022) - Fernández Muñoz, Beatriz; Lopez-Navas, Luis; Gonzalez Bermejo, María; Lomas Romero, Isabel María; Montiel Aguilera, Miguel Ángel; Campos Cuerva, Rafael; Arribas Arribas, Blanca; Nogueras, Sonia; Carmona Sánchez, Gloria; Santos González, Mónica
Abstract: Recent years have witnessed the introduction of ex vivo expanded dermal fibroblasts for several cell therapy and tissue-engineering applications, including the treatment of facial scars and burns, representing a promising cell type for regenerative medicine. We tested different in-house produced human platelet lysate (HPL) solutions against fetal bovine serum as supplements for in vitro fibroblast expansion by comparing cell yield, molecular marker expression, extracellular matrix (ECM) generation, genomic stability and global gene expression. Our in-house produced HPL supported fibroblast growth at levels similar to those for FBS and commercial HPL products and was superior to AB human serum. Cells grown in HPL maintained a fibroblast phenotype (VIM +, CD44 +, CD13 +, CD90 + ), ECM generation capacity (FN +, COL1 + ) and a normal karyotype, although gene expression profiling revealed changes related to cell metabolism, adhesion and cellular senescence. The HPL manufacturing process was validated within a GMP compliant system and the solution was stable at −80ºC and −20ºC for 2 years. Dermal fibroblasts expanded in vitro with HPL maintain a normal karyotype and expression of fibroblast markers, with only minor changes in their global gene expression profile. Our in-house produced GMP-HPL is an efficient, safe and economical cell culture supplement that can help increase the healthcare activity of blood transfusion centers through the re-use of transfusional plasma and platelets approaching their expiration date. Currently, our HPL solution is approved by the Spanish Agency of Medicines and Medical Devices and is being used in the manufacture of cell therapy products.Abbreviations: AB plasma: plasma group AB; ABHS: AB Human Serum; ABHS+GF: AB Human Serum supplemented with growth factors; ANOVA: Analysis of variance; ATMPs: Advanced Therapies for Medicinal Products; CPE: cytopathic effect; DEGs: Differentially expressed genes; DMEM: Dulbecco's modified Eagle's Medium; ECM: Extracellular matrix; ELISA: enzyme-linked immunosorbent assay; FBS: Fetal bovine serum; FDR: False discovery rate; FGF: Fibroblast growth factor; GMP: Good manufacturing practice; HPL: Human platelet lysate; HPL-CM: commercial human platelet lysate; MSCs: mesenchymal stem cells; NEAA: non-essential amino acids; P/S: penicillin/streptomycin; PBS: phosphate buffered saline; PC: leukodepleted platelet concentrate; PCR: polymerase chain reaction; PDGF: Platelet-derived growth factor; PDGFRA: Platelet-derived growth factor receptor alpha; qPCR: quantitative polymerase chain reaction; RNA: Ribonucleic acid; RT: Room temperature; TAC: Transcriptome analysis console; TGF-β: Transforming growth factor beta